2020
DOI: 10.1002/wer.1395
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sludge dewaterability and phosphate removal through a novel chemical dosing strategy using ferric chloride and hydrogen peroxide

Abstract: In this study, we replicated full‐scale centrifuge dewatering utilized in water resource recovery facilities (WRRFs) by using the Higgins modified centrifuge technique and demonstrated that analogous cake solid content and centrate suspended solids were attainable while applying a lower polymer dosage. Furthermore, we demonstrated a dramatic reduction in the concentration of phosphate (P) in anaerobically digested sludge (ADS) under various reaction conditions. H2O2 was employed to convert embedded iron in ADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Different treatment techniques (crystallization, precipitation, ion exchange, etc.) have been used for inorganic phosphorus removal [21][22][23] but traditional techniques are not well-suited for organic phosphates due to their unique structures. Natural polymers for phosphorus removal have not been extensively studied, but it was shown that adding a starch-based flocculant with FeCl 3 may save one-third of the total cost of pre-treatment while 90% of total phosphorus was reduced [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Different treatment techniques (crystallization, precipitation, ion exchange, etc.) have been used for inorganic phosphorus removal [21][22][23] but traditional techniques are not well-suited for organic phosphates due to their unique structures. Natural polymers for phosphorus removal have not been extensively studied, but it was shown that adding a starch-based flocculant with FeCl 3 may save one-third of the total cost of pre-treatment while 90% of total phosphorus was reduced [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reprecipitate phosphorus, an oxidizing agent such as hydrogen peroxide (H 2 O 2 ) is used to dissociate FeS. With partial oxidation, the free ferrous iron would react with orthophosphates to precipitate as vivianite, and with complete oxidation, the free ferrous iron is converted to ferric iron, producing HFOs and eventually removing orthophosphates from the liquid phase (Ghodsi et al, 2021). The application of H 2 O 2 in peroxide regenerated iron-sulfide control (PRI-SC) was described by Walton et al (2004) where H 2 O 2 is fed in the collections system at optimized rates to raw wastewaters freeing ferrous iron to oxidize spent iron (FeS), making that iron available to control sulfide generated downstream.…”
Section: Introductionmentioning
confidence: 99%
“…While phosphorus removal can be realized through both biological and chemical means, meeting such limits can be achieved through some level of chemical addition such as alum (e.g., Al 2 (SO 4 ) 3 .14H 2 O), ferric iron salts (e.g., FeCl 3 .6H 2 O), ferrous iron salts (e.g., Fe SO 4 .7H 2 O, FeCl 2 ), and in some cases calcium salts or lime (Conidi & Parker, 2016; Thistleton et al, 2002). Chemical phosphorus removal is recognized as a practical cost‐effective method compared to crystallization in fluidized bed pellet reactors or magnetic separation, with iron salts being more preferable and widely used considering that they are less expensive compared with aluminum salts, improve sludge dewaterability, limit corrosion, and minimize odor control issues arising from noxious hydrogen sulfide emissions (Ghodsi et al, 2021; van van Starkenburg et al, 1993; Walton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation